Convenient design method for customized implants based on bionic vein structure features - Wang, Lin; Geng, Weizhong; He, Kunjin; Guo, Kaijin (Frontiers in Bioengineering and Biotechnology, 2022)
Matching implants to bones is crucial for customized orthopedic medicine. Existing methods for designing customized implants predominantly adopt the parameterized deformation method that uses a fragmented representation of semantic parameters. Such a representation cannot provide information integration management and therefore restricts the retrieval of information regarding implant features and the improvement of customized design efficiency. Therefore, this paper proposes a rapid design method for customized implants based on bionic vein structure features. First, a bionic vein structure was designed to represent the implant type. Next, the bionic vein structure was represented by a digraph structure with the morphological and dimensional features. Finally, the implant model was rapidly built by retrieving the sketch and other modeling operation. Common implants such as the T-shaped plate, L-shaped plate, clover plate, and femoral stem prosthesis were used as explain or test cases. The experimental work shows that combining the traditional parametric deformation method with bionic vein structure features in our present method is flexible and efficient results, and can improve the efficiency of customized implant design.